Effects of SERCA and PMCA inhibitors on the survival of rat cochlear hair cells during ischemia in vitro - Amarjargal, N; Mazurek, B; Haupt, H; Andreeva, N; Fuchs, J; Gross, J (Physiological research, 2008)
An important mechanism underlying cochlear hair cell (HC) susceptibility to hypoxia/ischemia is the influx of Ca2+. Two main ATP-dependent mechanisms contribute to maintaining low Ca2+ levels: uptake of Ca2+ into intracellular stores via smooth endoplasmic reticulum calcium ATPase (SERCA) and extrusion of Ca2+ via plasma membrane calcium ATPase (PMCA). The effects of the SERCA inhibitors thapsigargin (10 nM-10 µM) and cyclopiazonic acid (CPA; 10-50 µM) and of the PMCA blockers eosin (1.5-10 µM) and o-vanadate (1-5 mM) on inner and outer hair cells (IHCs/OHCs) were examined in normoxia and ischemia using an in vitro model of the newborn rat cochlea. Exposure of the cultures to ischemia resulted in a significant loss of HCs. Thapsigargin and CPA had no effect. Eosin decreased the numbers of IHCs and OHCs by up to 25 % in normoxia and significantly aggravated the ischemia-induced damage to IHCs at 5 and 10 µM and to OHCs at 10 µM. o-Vanadate had no effect on IHC and OHC counts in normoxia, but aggravated the ischemiainduced HC loss in a dose-dependent manner. The effects of eosin and o-vanadate indicate that PMCA has an important role to play in protecting the HCs from ischemic cell death.
Keywords: Cell Survival; Calcium; vanadáty; PMCA; vnitřní vláskové buňky; Hair Cells, Auditory, Outer; Perilymph; Ischemia; vápník; Rat; novorozená zvířata; financování organizované; krysa rodu Rattus; Financing, Organized; Sarcoplasmic Reticulum Calcium-Transporting ATPases; Eosine Yellowish-(YS); zvířata; Organ of Corti; ATPasy přenášející vápník přes plazmatickou membránu; Hair Cells, Auditory, Inner; eosin; potkani Wistar; Animals, Newborn; sarkoplazmatická Ca2+-ATPáza; Plasma Membrane Calcium-Transporting ATPases; Rats, Wistar; ischemie; Vanadates; inhibitory enzymů; Rats; Animals; vnější vláskové buňky; Cortiho orgán; Enzyme Inhibitors; viabilita buněk; perilymfa